MRCP Versus ERCP in the Evaluation of Chronic Pancreatitis in Children: Which Is the Better Choice?. Issue 8 (September 2016) - Kolodziejczyk, Elwira; Jurkiewicz, Elzbieta; Pertkiewicz, Jan; Wejnarska, Karolina; Dadalski, Maciej; Kierkus, Jaroslaw; Woynarowski, Marek; Ryzko, Jozef; Oracz, Grzegorz
Abstract : Objectives: To evaluate the diagnostic accuracy of magnetic resonance cholangiopancreatography (MRCP) in the detection of chronic pancreatitis (CP)–specific changes in the pediatric population. Methods: The study included 48 children with pancreatic disorders subjected to both endoscopic retrograde cholangiopancreatography (ERCP) and MRCP within a 1- to 4-month interval. The sensitivity, specificity, positive predictive value, and negative predictive value of MRCP in the detection of CP-specific changes were determined using ERCP as a diagnostic standard. Results: Diagnostic ERCP pancreatograms were obtained in 41 (85.4%) of 48 patients and diagnostic MRCP images in all 48 children. The sensitivity and positive predictive value of MRCP were 77.1% and 90%, respectively, and its specificity and negative predictive value amounted to 50% and 27.3%, respectively. The patients with consistent results of MRCP and ERCP (ie, true-positive and true-negative cases) and individuals with incompatible results of the tests (ie, false-positive and false-negative cases) differed in terms of their median age at MRCP (14.17 vs 10.33 years) and median CP stage according to the Cambridge Scale (4 vs 2). Conclusions: Magnetic resonance cholangiopancreatography provides diagnostic information equivalent to ERCP in a large percentage of pediatric patients with CP and should be used as the imaging method of choice, especially if the likelihood of therapeutic intervention is low.